The Implementation of Independent Empowerment of Fisherwomen in Tanjung Batu Harapan Village of Muara Muntai District, Kutai Kartanegara Regency, East Kalimantan - Suryaningsi; Asikin, Nur (Salasika, 2020)
independence and empowerment of fisherwomen in Tanjung Batuq Harapan Village. The data sources were the Head of Muara Muntai Sub-district, the Head of Tanjung Batuq Harapan Village, fisherwomen, and villagers. The data were analyzed through several stages involving collection, data reduction, data presentation, and conclusions. The results of the study indicated that the independence and empowerment of fisherwomen in Tanjung Batuq Harapan Village were not optimally implemented. This could be seen through the fact that women multitasked themselves as wives who had to take care of their husbands and children as well as the breadwinners of their families. Meanwhile, the husbands' roles were mostly earning money for living with less attention to domestic matters. Nevertheless, the majority of fisherwomen in Tanjung Batuq Harapan were widows who felt marginalized by the infrastructure in their village.